Passion for art and passion for art? Ethnography of the practices and emotions in the organizational process of a circus in Canada - Oliveira, Josiane Silva de; Cavedon, Neusa Rolita (Revista de Administração da UFSM, 2019)
The objective of this paper is to understand how relationships between practices and emotions configure the organizational process of a circus, located in Montréal, Canada. We conduct a theoretical approach between the concepts of practices of the Michel de Certeau and organizational processes of Theodore Schatzki, discussing a policy approach to everyday life in organizations. We combine these discussions to debates about the political effects of emotions in social life. From an ethnographic study, we propose that the practices are built on the emotional politics of everyday life resulting in the production of social spaces hybrid in mobile organizational processes, such as the circus. Thus, it is possible to understand how organizational processes circus in the relationship between the practices that produce mobility and emotions which shape the social space, the result of a political struggle in the artistic field, showing the “passion for art” as a dimension of life collective of artists that organizes different practices in recognition of the circus as art in Canada.